Relation Between Circulating Inflammatory Chemokines and Vascular Characteristics in Healthy, Young Children - Eikendal, Anouk L. M. (J Am Heart Assoc, 2015)
BACKGROUND: Atherosclerosis begins in childhood with the occurrence of inflammatory vascular wall alterations that are detectable with B‐mode ultrasound. Chemokines appear to be involved in the development of these alterations given that they occur early in the atherosclerotic pathway as mediators of vascular inflammation. However, this has not extensively been investigated. Therefore, we studied in healthy young children whether chemokines monocyte chemotactic protein 1 (MCP‐1), regulated on activation normal T‐cell expressed and secreted (RANTES), and vascular and intercellular adhesion molecules (VCAM and ICAM) related to vascular characteristics of the carotid artery. METHODS AND RESULTS: We obtained demography, anthropometry, and overnight fasting plasma of 139 eight‐year‐old children of the Wheezing Illnesses Study Leidsche Rijn birth cohort. Carotid intima‐media thickness (CIMT), distensibility, and Young's Elastic Modulus (YEM) of the common carotid artery were measured sonographically. Chemokine plasma levels were assessed using a multiplex assay. We studied the relation between the chemokines and vascular characteristics using multivariable linear regression analyses with adjustments for sex, systolic blood pressure, homeostasis model assessment of insulin resistance, triglycerides, low‐density lipoprotein‐ and high‐density lipoprotein‐cholesterol. Of the studied chemokines, RANTES related to common carotid distensibility and YEM. One standard deviation increase in RANTES level related to a 5.45‐MPA (−1) (95% confidence interval [CI], −9.43, −1.39; P=0.01) decrease in distensibility and to a 5.55‐kPa increase in YEM (95% CI, 0.40, 10.85; P=0.03). RANTES did not relate to CIMT. MCP‐1, VCAM, and ICAM did not relate to any of the studied vascular characteristics. CONCLUSION: RANTES appears to be involved in the development of preatherosclerotic inflammatory vascular alterations already in healthy, young children. This may provide further insight into the early‐life origins of atherosclerosis.